Psychological Stress Induced Recurrent Genital Herpes: A Case Report - Jefrizal Wirman; Qaira Anum; Rina Gustia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Herpes simplex virus type 2 (HSV-2) infection can be caused by genital herpes with a high recurrence rate. Recurrent genital herpes affected patients’ quality of life. Precise management is needed to prevent the progression of the disease. Case presentation: This study reported a 34 years old male with recurrent genital herpes. The patient developed painful vesicles in the genital area, which turned into an ulcer. History of genital herpes and gonorrhoea urethritis were reported and had been treated. The patient had a history of having unprotected sexual intercourse with multiple partners and reported having psychological stress within 1 month. DLQI score was 12, and the DASS score was 5-85, which confirmed that the patient had anxiety. Vesicles and erosion were found in the genital area. Tzanck test showed multinucleated giant cells with borderline anti-HSV-2 IgG serologies in 2 occasional evaluations. Acyclovir 3x400 mg for 5 days was used as therapy, and no lesion was found at follow-up. Conclusion: Psychological stress was found to be a risk factor for recurrent genital herpes